State‐of‐the‐Art Fabrication of Microneedle Patches: A Mini‐Review on Emerging Techniques - Shah, Syed Waqas Ali; Li, Xingxing; Yuan, Hao; Shen, Huiling; Pan, Guifang; Xie, Hanhan; Shao, Jundong (MedComm - Biomaterials and applications, 2025)
Microneedle (MN) patches are an emerging platform in transdermal drug delivery, offering a minimally invasive, pain‐free alternative to conventional administration routes. Their performance, biocompatibility, and clinical potential are fundamentally influenced by the fabrication methods used. This mini‐review provides a critical overview of current and emerging MN fabrication techniques. Conventional approaches including micro‐molding (MM), microelectromechanical systems (MEMS) fabrication, laser micromachining, three‐dimensional (3D) printing, coating methods, and hydrogel‐forming technologies are discussed in detail. Additionally, innovative strategies such as electrospinning (Els) and bioprinting (BP) are examined for their ability to enable complex architectures and functional enhancements. Each technique is evaluated based on its operational principles, material compatibility, structural resolution, and scalability. Emphasis is placed on how these fabrication strategies affect mechanical strength, drug delivery efficiency, and clinical translation. The review also highlights the challenges in transitioning from laboratory‐scale development to commercial production. By integrating current advancements with future perspectives, this study provides a scientific foundation for guiding the rational design and large‐scale fabrication of MN systems. The manuscript aims to support innovation in biomedical, pharmaceutical, and cosmetic applications by offering a comprehensive assessment of the technological landscape.